Real-World Learning Based on SDG 6 to Enhance Students' Systems Thinking in Nature Schools - Ajeng Niamul Maula; Aa Juhanda; Jujun Ratnasari; Ridwansyah (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
To promote sustainable development, learning must provide real-world experiences that train students to think systemically. One essential competency to be developed is systems thinking ability. This study aims to analyze the systems thinking skills of students in a nature-based school through Real-World Learning (RWL) based on Sustainable Development Goal (SDG) 6, which focuses on clean water and sanitation. A quasi-experimental method with a non-equivalent control group design was employed. The study involved 42 eighth-grade students from Fathia Nature Junior High School in Sukabumi, assigned to experimental and control groups using a non-equivalent control group design. The findings showed that the average percentage scores of the experimental class were higher than those of the control class across all indicators. The highest indicators in the experimental class were recognizing hidden dimensions and making generalizations (each at 84%), while the lowest was identifying dynamic relationships (73%). The post-test results revealed a significant difference between the two classes (Sig. = 0.000 < 0.05). This study demonstrates that SDG 6-based RWL is effective in enhancing students’ systems thinking in environmental education.